Molecular, morphological and functional properties of tunnelling nanotubes between normal and cancer urothelial cells: New insights from the in vitro model mimicking the situation after surgical removal of the urothelial tumor - Resnik, Nataša; Baraga, Diana; Glažar, Polona; Jokhadar Zemljič, Špela; Derganc, Jure; Sepčić, Kristina; Veranič, Peter; Kreft, Mateja Erdani (Frontiers in Cell and Developmental Biology, 2022)
Tunnelling nanotubes (TNTs) are membranous connections that represent a unique type of intercellular communication in different cell types. They are associated with cell physiology and cancer pathology. The possible existence of TNT communication between urothelial cancer and normal cells has not yet been elucidated. Therefore, we analyzed TNTs formed by T24 cells (human invasive cancer urothelial cells) and normal porcine urothelial (NPU) cells, which serve as surrogate models for healthy human urothelial cells. Monocultures and cocultures of NPU and T24 cells were established and analyzed using live-cell imaging, optical tweezers, fluorescence microscopy, and scanning electron microscopy. TNTs of NPU cells differed significantly from TNTs of T24 cells in number, length, diameter, lipid composition, and elastic properties. Membrane domains enriched in cholesterol/sphingomyelin were present in TNTs of T24 cells but not in NPU cells. The TNTs in T24 cells were also easier to bend than the TNTs in NPU cells. The TNTs of both cell types were predominantly tricytoskeletal, and contained actin filaments, intermediate filaments, and microtubules, as well as the motor proteins myosin Va, dynein, and kinesin 5B. Mitochondria were transported within TNTs in living cells, and were colocalized with microtubules and the microtubule-associated protein dynamin 2. In cocultures, heterocellular TNTs were formed between NPU cells and T24 cells and vice versa. The presence of connexin 43 at the end of urothelial TNTs suggests a junctional connection and the involvement of TNT in signal transduction. In this study, we established a novel urothelial cancer-normal coculture model and showed cells in the minority tend to form TNTs with cells in the majority. The condition with cancer cells in the minority is an attractive model to mimic the situation after surgical resection with remaining cancer cells and may help to understand cancer progression and recurrence. Our results shed light on the biological activity of TNTs and have the potential to advance the search for anticancer drugs that target TNTs.